2020
DOI: 10.3390/molecules26010050
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of CO2 Promoted by Silicon-Activated H2S: Origin and Implications

Abstract: Unlike the usual method of COx (x = 1, 2) hydrogenation using H2 directly, H2S and HSiSH (silicon-activated H2S) were selected as alternative hydrogen sources in this study for the COx hydrogenation reactions. Our results suggest that it is kinetically infeasible for hydrogen in the form of H2S to transfer to COx at low temperatures. However, when HSiSH is employed instead, the title reaction can be achieved. For this approach, the activation of CO2 is initiated by its interaction with the HSiSH molecule, a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In addition, the H 2 O molecule has been found to act as a hydrogen donor in CO 2 reduction. Liu [13] found that the transfer of hydrogen to CO x in the form of H 2 S at low temperatures was not feasible kinetically, while the adsorption of CO 2 on the surface of silicon-activated H 2 S can produce HCOOH.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the H 2 O molecule has been found to act as a hydrogen donor in CO 2 reduction. Liu [13] found that the transfer of hydrogen to CO x in the form of H 2 S at low temperatures was not feasible kinetically, while the adsorption of CO 2 on the surface of silicon-activated H 2 S can produce HCOOH.…”
Section: Introductionmentioning
confidence: 99%